Public Policy Innovation in Objectifying Excellent Service - Hayat Hayat (Universitas Padjadjaran, 2024)
This research aims to investigate the correlation between policy innovation and the quality of public services with a focus on enhancing the welfare of the community, highlighting the urgency of policy innovation as a response to the dynamics of the global environment and society. The study identifies innovative models that suit the specific needs of the community, encourages active participation in the policy-making process, and provides guidance for the development of progressive policies. Additionally, there are challenges in policy implementation, especially in the context of bureaucracy and public dissatisfaction. The applied research method is qualitative descriptive, involving steps such as identifying phenomena based on theoretical references, formulating research objectives, collecting and analyzing data using a qualitative descriptive approach, and formulating conclusions. The research emphasizes the central role of policy innovation in achieving excellent public services. The implementation of innovative models, such as the Public Service Mall (MPP) and Community Satisfaction Index (IKM), demonstrates positive potential in improving the quality of public services. The importance of responsive and effective governance in the context of public policy to provide better services to the community and reduce the gap between social changes and existing regulations is highlighted. This study contributes to the practical and theoretical understanding of how policy innovation can play a role in improving the quality of public services and achieving sustainable development goals.